Human umbilical cord perivascular cells exhibit enhanced cardiomyocyte reprogramming and cardiac function after experimental acute myocardial infarction - Yannarelli, Gustavo Gabriel (2013)
We were interested in evaluating the ability of the mesenchymal stromal cell (MSC) population, human umbilical cord perivascular cells (HUCPVCs), to undergo cardiomyocyte reprogramming in an established co-culture system with rat embryonic cardiomyocytes. Results were compared with human bone marrow-derived (BM) MSCs. The transcription factors GATA4 and Mef2c were expressed in HUCPVCs but not BM-MSCs at baseline, and at 7 days increased 7.6 and 3.5-fold respectively, compared with BM-MSCs. Although cardiac-specific gene expression increased in both cell types in co-culture, up-regulation was more significant in HUCPVCs, consistent with Mef2c-GATA4 synergism. Using a lentivector with eGFP transcribed from the a-myosin heavy chain ( a-MHC) promoter, we found that cardiac gene expression was greater in HUCPVCs than BM-MSCs after 14d co-culture (52±17% vs 29±6%, respectively). A higher frequency of HUCPVCs expressed a-MHC protein compared with BM-MSCs (11.6±0.9% vs 5.3±0.3%) however, both cell types retained MSC-associated determinants. We also assessed the ability of the MSC types to mediate cardiac regeneration in a NOD/SCID(gnull) mouse model of acute myocardial infarction (AMI). Fourteen days after AMI, cardiac function was significantly better in celltreated mice compared with control animals and HUCPVCs exhibited greater improvement. Although human cells persisted in the infarct area, the frequency of a-MHC expression was low. Our results indicate that HUCPVCs exhibit a greater degree of cardiomyocyte reprogramming but that differentiation for both cell types is partial. We conclude that HUCPVCs may be preferable to BM-MSCs in the cell therapy of AMI.